SHOOTING DOWN CIVILIAN AIRCRAFT: ILLEGAL, IMMORAL AND JUST PLANE STUPID - Stephen Brown, Rory (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2007)
This paper discusses whether it should be legal for a state to shoot down a civilian plane, converted by terrorists into a deadly suicide missile. Is it justifiable to kill innocent airline passengers to save lives on the ground? Can ‘human arithmetic’ be a legal calculus? To decide how a liberal democracy should respond to a repeat of September 11, the author examines several relevant registers of law, and attempts to discern helpful principles in murky cases of past interceptions of military and civilian aircraft. After concluding that law can provide no definitive answer, and, indeed, has shied away from sodoing, he turns to morality, tending to find her more phlegmatic in this distasteful inquiry. At the outset, it should be noted that the suggestion here is not that threatening passenger aircraft should never be shot out of the sky; rather, that such resorts should be legally prohibited. That is, in certain circumstances, interception of a civil flight might well be the best thing to do, the most laudable action, yet remain a wrong, a lesser evil, punishable in law. In other words, in extreme cases, the shooting of a plane may be morally justified, but it should not be legally excused - this does not entail that morality and law sourly part company; rather that they develop and refine their understanding; that the rule of law and integrity of society may be preserved, if not restored, by the seemingly Draconic punishment of heroes. It is hoped that the quarrying of a specific situation might extract valuable lessons of broader use. The author’s preference here is to leave these more general lessons unexpressed.